KEPEMILIKAN MANAJERIAL, KUALITAS AUDITOR DAN MANAJEMEN LABA - Agung Prayogi (Jurnal Ilmiah Raflesia Akuntansi, 2022)
In a village financial system that is shifted to the allocation of village funds to regional agencies to increase the APBN through regional original income. The case study carried out was at the Village Office location in Gejagan Village, Loceret District, Nganjuk Regency by monitoring the application system for processing and financial arrangements in allocating village funds to various activities in implementing existing activities in the village. Meanwhile, this village uses the application of a good governance system or in the Latin term meaning good government by linking an accountability of village funds into activities that have been designed since the planning system was created for a program to be carried out. Although in its implementation the village government is required to have an aspect of good governance, where one of the main characteristics or elements of good governance is accountability. Accountability itself is a form of responsibility for carrying out the organization's mission in achieving the goals that have been set through the medium of accountability which is carried out periodically. The allocation of village funds is basically financial assistance from the Regency Government, Provincial Government, and Central, City Government to the Village Government sourced from the APBN, Provincial APBD, Regency/Municipal APBD which is channeled through the village treasury in the context of implementing Village Governments that have events. specific in each village.